Human breast adipose tissue: characterization of factors that change during tumor progression in human breast cancer - Fletcher, Sabrina Johanna (2017)
Background: Adipose microenvironment is involved in signaling pathways that influence breast cancer. We aim to characterize factors that are modified: 1) in tumor and non tumor human breast epithelial cell lines when incubated with conditioned media (CMs) from human breast cancer adipose tissue explants (hATT) or normal breast adipose tissue explants (hATN); 2) in hATN-CMs vs hATT-CMs; 3) in the tumor associated adipocytes vs. non tumor associated adipocytes. Methods: We used hATN or hATT- CMs on tumor and non-tumor breast cancer cell lines. We evaluated changes in versican, CD44, ADAMTS1 and Adipo R1 expression on cell lines or in the different CMs. In addition we evaluated changes in the morphology and expression of these factors in slices of the different adipose tissues. The statistical significance between different experimental conditions was evaluated by one-way ANOVA. Tukey’s post-hoc tests were performed within each individual treatment. Results: hATT-CMs increase versican, CD44, ADAMTS1 and Adipo R1 expression in breast cancer epithelial cells. Furthermore, hATT-CMs present higher levels of versican expression compared to hATN-CMs. In addition, we observed a loss of effect in cellular migration when we pre-incubated hATT-CMs with chondroitinase ABC, which cleaves GAGs chains bound to the versican core protein, thus losing the ability to bind to CD44. Adipocytes associated with the invasive front are reduced in size compared to adipocytes that are farther away. Also, hATT adipocytes express significantly higher amounts of versican, CD44 and Adipo R1, and significantly lower amounts of adiponectin and perilipin, unlike hATN adipocytes. Conclusions: We conclude that hATT secrete a different set of proteins compared to hATN. Furthermore, versican, a proteoglycan that is overexpressed in hATT-CMs compared to hATN-CMs, might be involved in the tumorogenic behavior observed in both cell lines employed. In addition, we may conclude that adipocytes from the tumor microenvironment show a less differentiated state than adipocytes from normal microenvironment. This would indicate a loss of normal functions in mature adipocytes (such as energy storage), in support of others that might favor tumor growth.